Treatable traits in copd – a proposed approach - Cardoso, João (2021)
Funding Information: Medical writing support for this article was provided by Paula Pinto, PhD, of PMA – Pharmaceutical Medicine Academy and was funded by Bial. All authors contributed equally to this work and should be considered co-first authors for this study. Funding Information: This article was funded by Bial. Bial provided all necessary scientific bibliography and funded medical writing support and publishing charges. The authors did not receive direct funding for the writing of this article. Publisher Copyright: © 2021 Cardoso et al.